(untitled) (Research, Society and Development, 2022)
Introduction: With the pandemic of the new coronavirus, the daily life of a large part of the population has undergone significant changes and, because of the isolation generated in the period of quarantine, violence against women has increased considerably, as the time of exposure to your abuser grew. Objective: To analyze the impact of the COVID-19 pandemic on women in situations of domestic violence. Method: Integrative literature review carried out through searches LILACS, BDENF, MEDLINE and SciELO databases. National and international articles that addressed the topic of domestic violence in times of a pandemic were included in the study. Results: After selection by analyzing titles and respective abstracts, adopting exclusion criteria, extracting those in duplicate and those that were not in line with the proposed theme, 26 publications remained. The reading was carried out in full and thus they were categorized into 5 relevant themes because they stand out in the content of the publications. Conclusion: The selected articles show the triggering factors of domestic violence along with their impacts, the versatile strategies and organizational measures adopted to face the problem and the importance of nursing professionals and health units in the care of women victims of conjugal aggression.